A method to analyze the mode of action of hormones using conidiation rhythm of Neurospora. - K. Hasunuma; K. Tomita; K. Mitsouka; Y. Shinohara; T. Nakamura (Fungal Genetics Reports, 1986)
A method to analyze the mode of action of hormones using conidiation rhythm of Neurospora.